Review on Pickering emulsions stabilized by adsorbed nanoparticles: Structure, Thermodynamics, Cage Effect and Subdiffusion - M Benhamou; S El-Moudny (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2017)
In this review paper, we report on some very recent findings dealt with the oil-in-water Pickering emulsions, stabilized by a strong adsorption of charged solid nanoparticles on the surface of the oil-droplets. Here, we are concerned with three important questions: (1) Structure and thermodynamics of these emulsions, (2) cage effect and subdiffusion phenomenon within them, and (3) spherical diffusion of anchored nanoparticles on the curved oil/water interface. For the study, the emulsions are regarded as colloidal solutions, where the clothed oil-droplets play the role of charged soft-colloids, and in addition, the adsorbed nanoparticles are assumed to be point-like. For question (1), we recall the essential steps allowing the determination of the structure-factor and the spatial-correlation function, and the thermodynamic properties, as pressure, internal energy, and thermal compressibility of these emulsions. To this end, the adopted pair-potential is that of Sogami-Ise combining repulsive and attractive forces, and use is made of the so-called Integral Equation Method. The question (2) deals with a quantitative investigation of the clothed oil-droplets dynamics (cage effect and subdiffusion), using a Generalized Langevin Equation, which is successfully tested by Molecular Dynamic Simulations. The question (3) is concerned with an exact study of the spherical diffusion of anchored nanoparticles on the surface of the dispersed oil-droplets. Finally, we precise the major role played by grafted polymers onto the spherical oil/water interface.